Evaluation of Domestic Solid Waste Management in Cai Rang District, Can Tho City, Vietnam - Truong Hoang Dan; Le Tran Thanh Liem; Nguyen Thi Bich Lua; Le Thi Diem Mi (Indonesian Journal of Environmental Management and Sustainability, 2023)
The study was conducted to evaluate the management of domestic solid waste in Cai Rang district, Can Tho city. The study conducted sampling of domestic solid waste from 20 households in four wards Le Binh, Hung Phu, Ba Lang, and Tan Phu within 07 days from March 6 to 12, 2023. At the same time, three groups of subjects including 120 households, 3 Environmental Managers, and 3 employees of Urban Environment Joint Stock Company were interviewed to collect information. The result showed that the average domestic solid waste generation coefficient reached 0.28 kg/person/day, and the amount of domestic solid waste generated can reach about 11,027.3 tons by the end of 2023. Of which, up to 91% of the volume of domestic solid waste was recyclable, including 52% of biodegradable organic waste, and 39% of recyclable waste. As for domestic solid waste management, there was still a limitation in classifying waste at source, this rate only fluctuates between 43.4-86.7%. Besides, the rate of households registered for domestic solid waste collection service had a difference between urban and rural areas, fluctuating from 76.7-96.7%. After being collected, domestic solid waste was transported to the Can Tho household waste incineration plant (EB plant). Meanwhile, the remaining amount of domestic solid waste was treated using unsanitary landfill methods, and thrown into rivers, causing environmental pollution, and public health. Although propaganda activities related to domestic solid waste management were carried out in four wards in Cai Rang district, Can Tho city. However, the level of implementation of these activities was not regular. From that, the study identified a number of difficulties in domestic solid waste management, including solid waste that was not completely classified at source, and garbage collection services that were not organized throughout the area. The district lacked specialized waste collection vehicles after classification, and public propaganda, and education work were limited. This research will help local authorities come up with specific solutions to improve the quality of solid waste management in Cai Rang district, Can Tho city.